Investigating Islamic Religious Education Teacher Beliefs Toward Multimedia Learning - Muslimah, Muslimah (Program Studi Pendidikan Agama Islam, 2024)
Teachers' beliefs regarding multimedia learning are essential. This study aims to explore teachers' beliefs about multimedia learning in Islamic Religious Education (PAI) at Senior High School in Palangka Raya, Central Kalimantan, Indonesia. This research employed the mix-method QUAN-QUAL, the exploratory sequential design. Nine teachers were involved based on a purposive sampling technique. Twenty-three questionnaire items were constructed to collect the quantitative data. An interview guide was used to collect the qualitative data. The quantitative data was collected through a cross-sectional survey, and the qualitative data was collected through a semi-structured interview. The SPSS version 26 was utilized to analyze the quantitative. Moreover, thematic or coding analysis was used to analyze qualitative data. Multimedia learning was shown to have excellent potential to improve students' learning experiences. With proper implementation and adequate support, multimedia learning could effectively improve the quality of Islamic Religious Education. However, some challenges must be faced to achieve optimal learning outcomes.